1983
DOI: 10.1002/jmv.1890110409
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to fastidious faecal adenoviruses (species 40 and 41) in sera from children

Abstract: Three hundred and seventy-seven single sera from children in the United Kingdom, Hong Kong, New Zealand, Gambia, Guatemala, and Kuwait were tested for antibodies to fastidious fecal adenoviruses (species 40 and 41) by neutralisation test using a variant of Ad41 (Ad41a). All children were less than 12 years of age, and at least 41.1% of the total tested had antibodies. One hundred and fifty-four of these sera were collected during the 1960s from London children attending day nurseries, and 54.5% had antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 16 publications
1
41
0
1
Order By: Relevance
“…Fecal samples of chimpanzees (n ϭ 113) were tested, but sequences attributable to HAdV-F or -G were not detected (data not shown). We concluded from these findings that HAdV-F and -G do not genuinely occur in chimpanzees, and since HAdV-F viruses are endemic in most countries (29,50), the single chimpanzee HAdV-F virus (PtroAdV-3) with 99.8% identity to HAdV-40 is most likely the result of a very recent human-to-chimpanzee interspecies transmission event. In addition, the obvious lack of HAdV-G in chimpanzees further supports the above notion that HAdV-52 may have originated from an OWM.…”
Section: Vol 85 2011 Novel Adenoviruses In Wild Primates 10781mentioning
confidence: 92%
“…Fecal samples of chimpanzees (n ϭ 113) were tested, but sequences attributable to HAdV-F or -G were not detected (data not shown). We concluded from these findings that HAdV-F and -G do not genuinely occur in chimpanzees, and since HAdV-F viruses are endemic in most countries (29,50), the single chimpanzee HAdV-F virus (PtroAdV-3) with 99.8% identity to HAdV-40 is most likely the result of a very recent human-to-chimpanzee interspecies transmission event. In addition, the obvious lack of HAdV-G in chimpanzees further supports the above notion that HAdV-52 may have originated from an OWM.…”
Section: Vol 85 2011 Novel Adenoviruses In Wild Primates 10781mentioning
confidence: 92%
“…The 112 samples of which stored specimens remained, represented 88 % of the total number of samples positive for adenovirus by electron microscopy over the 2-year period. Adenovirus serotype 41 has been divided into two strains 41a and 41p on the basis of Sma I digestion patterns (Kidd, Banatvala & de Jong, 1983). All adenovirus 41 detected in Newcastle throughout the 2-year period of the survey were 41a strains.…”
Section: Evaluation Of the Electrophoretic Methods In Diagnosismentioning
confidence: 99%
“…Adenoviruses implicated in acute enteric disease, grow poorly and often not at all in the cells routinely used for culture (Brandt et al 1979). These viruses have been designated serotypes 40 and 41 (de Jong et al 1983). In the absence of readily available type-specific antisera, and difficulties in virus culture, direct serotyping by neutralization or by other methods such as ELISA are inapplicable.…”
Section: Introductionmentioning
confidence: 99%
“…Kidd et al (193) obtained 377 serum samples from children under the age of 12 years living in the United Kingdom, New Zealand, Hong Kong, Guatemala, Gambia, and Kuwait. By a neutralization test, they found that at least 33% of the sera from the United Kingdom, Hong Kong, and the isolated country of Gambia had neutralizing antibody to 40 and 41.…”
Section: Immunologymentioning
confidence: 99%